Visual focus and physiological parameters of air pistol shooters under different conditions: a psychophysiological perspective - Güler, G.; Simsek, D.; Tuncer, S.; Mon-López, D. (International Journal of Sport and Exercise Psychology, 2025)
The aim of this study was to examine visual focus, attention processes, and physiological parameters of air pistol shooters under different pressure conditions. Thirty-two (n = 9 elite, n = 11 intermediate and n = 12 novice) air pistol shooters performed 10 shots in both control condition and pressure condition. Quiet eye (QE) duration, pupil size, skin conductance (SC) and heart rate (HR) were recorded simultaneously during shooting. SC and HR values were significantly higher in pressure condition compared to control condition; however, QE duration did not change in pressure condition for all three groups. Interestingly, the pupils of the elite group had greater dilation in control condition than in pressure condition; however, no differences were found for the novice and intermediate groups. The elite group had lower HR and greatest cardiac deceleration. In both control and pressure conditions, differences in SC values were observed between consecutive phases in all three groups. Elite and intermediate groups had longer QE durations compared to the novice group in both conditions, but no differences were found between elite and intermediate groups. In control condition, elite and intermediate groups had more pupil dilation in QE duration. Low HR and optimal QE duration are necessary for performance. Decreases in SC and HR and the dilation of pupil in the aiming phase are related to attention processing. Shooters are advised to train their visual focus to direct attention toward external rather than internal stimuli. Additionally, it is recommended that this visual focus be maintained for an optimal duration.